Relationships with Language and National Culture (comparative analysis) - Khojumyan , Bella (Bulletin of Yerevan University B: Philology, 2025)
The article is devoted to the comparative analysis of Russian and Armenian somatic phraseological units with the purpose of identifying the correspondences and differences between them. An attempt was made to establish a connection between them. An attempt was made to establish a connection between non-verbal language symbols and the corresponding phraseological units. The mentioned thematic group of phrases was specially chosen for the study, because it has an obvious human-centered orientation and for that reason is widely represented in all languages. The study was completely carried out under linguistic and cultural studies, applying the comparative method.Based on the study of specific material, we come to the conclusion that the observed discrepancies between the analyzed units in the two languages ​​are mainly associated with national identity, cultural traditions and the national mentality of the speakers of the compared languages.